PERANCANGAN DAN PEMBUATAN SISTEM KEAMANAN TERINTEGRASI PADA KENDARAAN BERBASIS MIKROKONTROLER ATMEGA328 - Jeki Cara Rusadi; Yasdinul Huda (Universitas Negeri Padang, 2019)
This research is motivated by the development of a security system on vehicles to reduce criminal acts such as theft, robbery and legality. However, security systems such as alarms and double locks still do not guarantee vehicle safety, because there is no notification to the user when the vehicle is stolen and cannot know the face of the person who stole the user's vehicle. The purpose of this Final Assignment is to apply ATMega328 microcontroller-based technology designed by making integrated hardware and security system software on motorized vehicles. The overall system design and manufacturing process uses the Reserve Engineering method by following several stages, namely: 1) designing the system, 2) designing the hardware, 3) designing the software, 4) the physical design of the tool and making the tool. From the results of the design and manufacture of an integrated security system on motorized vehicles it can be concluded that this tool can work well using the ATMega328 microcontroller as the center of the controller. To turn on the motor, the tool can recognize users with RFID RC522 tags that have been registered. In this tool the User can also find out the position of the vehicle when the vehicle is stolen via text messages and Google Maps with the internet network. When a user is banned by pressing the anti-lock push button, the system can notify the family via a short message. Support from this tool can turn off the vehicle remotely by sending the message